The new human rights movement : reinventing the economy to end oppression - Peter Joseph, 1978- (2017)
Society is broken. We can design our way to a better one. In our increasingly interconnected world, self-interest and social-interest are rapidly becoming indistinguishable. If the oceans die, if society fractures, or if global warming spirals out of control, personal success becomes meaningless. But our broken system incentivizes behavior that only makes these problems worse. If true human rights progress is to be achieved today, it is time we dig deeper-rethinking the very foundation of our social system. In this engaging, important work, Peter Joseph, founder of the world's largest grassroots social movement in the world-The Zeitgeist Movement-draws from economics, history, philosophy, and modern public-health research to present a bold case for rethinking activism in the 21st century. The conventional wisdom views poverty, social oppression, and the growing loss of public health as unfortunate and immutable side effects of our way of life. The New Human Rights Movement argues that these outcomes are, in fact, contrived-only natural to our outdated economic system. Social activists can never succeed in dramatically improving human life on this planet until they understand the structural reasons these problems exist. Arguing against the long-standing narrative of universal scarcity and other pervasive, legitimizing myths that defend the current state of affairs, The New Human Rights Movement ultimately presents the case for an updated economic approach. Joseph explores the potential of this grand social shift and how we can design our way to a post-scarcity world-a world where poverty doesn't exist and the human family has become truly sustainable. The New Human Rights Movement reveals the critical importance of a unified activism in this direction, through understanding and working to alter the inherent injustice of our current social system. This book not only warns against what is in store if we continue to ignore our broken society but also reveals the positive future possible if we succeed. Will you join the movement?
System-bound : realizing relationships -- Beyond the pale : our social mythology -- Structural bigotry : the economics of oppression -- Public health : spectrum of disorder -- Designing out : where we go from here -- Appendix A: Post-scarcity potentials -- Appendix B: Economic calculation and broad system conception.
"Distributed to te trade by Two Rivers Distribution, an Ingram brand"--Title page verso.
Includes bibliographical references.
Keywords: Human rights movements; Human rights -- Economic aspects; Business and politics; Business and politics; Human rights -- Economic aspects; Human rights movements; NON - FICTION